Perundungan Pada Peserta Didik SMP Negeri Di Pontianak Selatan Tahun Ajaran 2022/2023: Studi Cross-Sectional - Evan, Teoderus; Buwono, Sri; Karolina, Venny; Atmaja, Thomy Sastra (Jurnal Ilmiah Wahana Pendidikan, 2024)
This study aims to determine the level of experience of being bullied, the level of experience of bullying, the attitudes of students towards bullying and the relationship between the experience of being bullied (being a victim) and the experience of being a perpetrator of bullying among junior high school students in South Pontianak District in the 2022/2023 academic year. The research approach used is quantitative with survey method. The sample in this study were 377 junior high school students in South Pontianak District who were obtained using the slovin formula with cluster sampling technique and data collection tool in the form of a questionnaire. Data analysis techniques using descriptive statistics, data normality test and product moment correlation test. The results showed that: (1) the level of bullying victims among junior high school students in South Pontianak District (67.6%) was in the moderate category; (2) the level of bullying perpetrators among junior high school students in South Pontianak District (71.4%) was in the moderate category; (3) the level of student responses to bullying among junior high school students in South Pontianak District (70.8%) was in the moderate category; (4) there is a positive and significant relationship between the experience of being bullied (victim) and being a perpetrator of bullying among junior high school students in South Pontianak District in the 2022/2023 academic year, namely p=0.00<0.05 with r=0.36, meaning, students who have experienced bullying tend to become perpetrators of bullying.